2021
DOI: 10.4081/jphr.2021.2185
|View full text |Cite
|
Sign up to set email alerts
|

Intervention Empowerment of Families in Preventing and Controlling Overweight and Obesity in Children: A Systematic Review

Abstract: There have been an increasing overweight and obesity in very anxious children. Furthermore, obesity is a condition that occurs due to the accumulation of excess or abnormal fat. This disorder is believed to be the most significant public health problem that affects children in the 21st century. This study aimed to examine the literature review, articles and research results analyzing the effectiveness of family or parent empowerment interventions through health education. Many research articles were searched o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…The FIVALIN project concluded that by employing a multi-pronged behavioral approach that targets healthy eating, physical activity, screen time, sleep quality and duration, and psychological well-being, childhood obesity can be prevented in economically deprived families [45]. According to the data, lowering one's BMI is most closely related to lowering one's total cholesterol, triglycerides, low density lipoprotein cholesterol, and diastolic and systolic blood pressure [46][47][48].…”
Section: Discussionmentioning
confidence: 99%
“…The FIVALIN project concluded that by employing a multi-pronged behavioral approach that targets healthy eating, physical activity, screen time, sleep quality and duration, and psychological well-being, childhood obesity can be prevented in economically deprived families [45]. According to the data, lowering one's BMI is most closely related to lowering one's total cholesterol, triglycerides, low density lipoprotein cholesterol, and diastolic and systolic blood pressure [46][47][48].…”
Section: Discussionmentioning
confidence: 99%
“…The most effective way of preventing and controlling overweight and obesity is through family empowerment, including parental knowledge about nutrition, its influence on food choice, eating patterns, sedentary habits, and physical activity. The beliefs and parent's lifestyle and health promotion are also of vital importance due to learning by imitation [77]. Interestingly, parentonly interventions had a similar effect compared with parent-child interventions in children 5 to 11 years [78].…”
Section: Psychosocial and Parental Influencementioning
confidence: 92%
“…Childhood is regarded as the most important period of life affecting adulthood. Health problems or illnesses during this period would be brought to maturity or become a risk factor for the onset of diseases in adulthood [77]. The family and environment provide a great impact on social, cognitive, behavioral, and health aspects, including overweight and obesity.…”
Section: Psychosocial and Parental Influencementioning
confidence: 99%
“…Therefore, we tried to use a biopsychosocial framework that is different from previous interventions for childhood obesity intervention. The biopsychosocial framework for understanding obesity showed that the biological, psychosocial, and practical factors greatly contributed to the weight status of children, including the demographic and family characteristics, lifestyles, and environment of children ( 10 , 11 ). For example, the ultra-processed, energy-dense, and nutrient-poor foods exposure ( 12 ), as well as the declined opportunities for physical activity could lead to an unhealthy lifestyle and subsequent adverse health outcomes ( 13 ).…”
Section: Introductionmentioning
confidence: 99%